The Role of Wisdom and Patience in Islamic Education: Insights from QS. Al-Kahf Verses 60–82 - Permana, Rizal; Surahman, Cucu; Sumarna, Elan; Buchori, Buchori; Fauziah, Wafiq Nur; O’gli, Sodiqov Ulug’bek G’ulomjon (Arfannur: Journal of Islamic Education, 2025)
This article analyzes the interaction between teachers and students through the story of Prophet Moses and Khidr in QS. Al-Kahf verses 60–82. Using a qualitative approach and literature study method, it draws insights from the interpretations of Jalalain and Ibn Kathir to highlight the educational values of wisdom and patience. The study organizes its findings into three areas: character development (patience, refraining from quick judgment, recognizing limitations), pedagogical approaches (dialogue, application of wisdom, experiential learning), and the creation of an inclusive learning environment. The examination of key events such as the perforated boat, the killing of the young man, and the repair of the wall demonstrates the importance of patience in facing situations that seem illogical. These lessons offer practical implications for Islamic Religious Education (PAI), supporting teachers in making mature decisions and guiding students towards emotional, cognitive, and spiritual growth. Integrating these values into education fosters a reflective, supportive, and thoughtful learning atmosphere, enriching both the intellect and character in accordance with Islamic teachings